Malaria Prevention and Eradication Program Towards Malaria-Elimination in West-Seram (Indian Journal of Forensic Medicine & Toxicology, 2020)
Malaria is a health problem in the world spread in 95 countries. The research objective describes the evaluation of malaria-prevention and eradication programs including inputs, processes, and outputs using qualitative approach. Data were collected by in-depth interview. Research informants were 1 key-informants and 4 supporting-informants. Malaria-elimination program in West-seram District based on the guidelines of the Ministry of Health of the Republic of Indonesia and operationally outlined in the form of a technical guide. Case surveillance has not been carried out. Malaria vector control was done by eradicating mosquito nests and using mosquito nets containing insecticides. Cross-program and cross-program cooperation had been going well, but cross-sectoral collaboration, still needs to be improved. The funding was largely supported by donor agencies namely the Global Fund for AIDs, TBC, and Malaria (GF-ATM) while Government of West-Seram allocates microscopic slide examination costs. It is necessary to increase health personnel, facilities and infrastructure, discovery, prevention, and case management.
Keywords: malaria, elimination, evaluation, prevention, eradication